PELAKSANAAN PRINSIP PARTISIPASI PADA PELAYANAN KESEHATAN PADA RSUD DI KALIMANTAN SELATAN - Erlina Erlina (Faculty of Law, Universitas Riau, 2018)
Research on the principle of participation in health services is conducted on 14 regional hospitals in South Kalimantan using socio legal research methods. The data used are primary data obtained through questionnaires, interviews and observation and secondary. Implementation of the principle of participation by the technique of scoring the questionnaire is done by simple statistical data analysis. Implementation of the principle of participation of 14 (fourteen) regional hospitals in South Kalimantan is on average not accomplished with a percentage below 66.67. Implementation of the principle of good governance in the provision of health services through local hospitals has major constraints that are generally caused by the ethics of public services, public perceptions and common understanding, culture and characteristics of local communities, as well as the mastery of information technology in creating a good two-way relationship between public and public servants served.Keywords : Good Governance, Participation, Health Public Service